KEKERASAN DAN KETAHANAN KOROSI LAPISAN KERAS DI ATAS PERMUKAAN BAJA KARBON - Yunita Sari; Akmal Nashrullah; Sopiyan (Universitas Negeri Jakarta, 2022)
Low carbon steel is widely applied to make heavy equipment, such as bucket excavators because it has a combination of material properties such as strength, ductility, corrosion resistance, and good formability. The use of this excavator bucket requires high strength and high corrosion resistance. Because the excavator bucket always rubs against the ground, it is necessary to do hard facing to increase the hardness of this excavator bucket. This research examines the effect of coating and heat treatment on low carbon steel to increase hardness and corrosion resistance. The plating process uses manganese alloy steel and chrome alloy steel, then heat-treated to a temperature of 1000°C and holding time for 10 minutes, then cooled using water media. From the test results, it was found that coating using chrome alloy steel has higher hardness and corrosion resistance than coating using manganese alloy steel because chrome is harder and corrosion-resistant than manganese.